2008
DOI: 10.1111/j.1572-0241.2007.01778.x
|View full text |Cite
|
Sign up to set email alerts
|

Technical Performance of Colonoscopy: The Key Role of Sedation/Analgesia and Other Quality Indicators

Abstract: In usual clinical practice, the use of sedation/analgesia, the colon-cleansing quality, the endoscopist experience, and some features related to the colonscopy setting decisively influence the quality of colonoscopy. These factors indicate the targets of future corrective measures to boost the quality of this examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
122
1
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(146 citation statements)
references
References 35 publications
12
122
1
11
Order By: Relevance
“…35 A grave concern in the U.S. regarding unsedated colonoscopy is the belief that the procedure is painful. [10][11][12] Indeed, worldwide the success rate of unsedated colonoscopy have been reported to be 67% 36 , 76% 30,37 , 78% 31,38 , 81% 39,40 , 82% 41 and 83%. 41 A novel method of water infusion in lieu of air insufflation significantly improved the success rate of cecal intubation to 97% in an observational study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…35 A grave concern in the U.S. regarding unsedated colonoscopy is the belief that the procedure is painful. [10][11][12] Indeed, worldwide the success rate of unsedated colonoscopy have been reported to be 67% 36 , 76% 30,37 , 78% 31,38 , 81% 39,40 , 82% 41 and 83%. 41 A novel method of water infusion in lieu of air insufflation significantly improved the success rate of cecal intubation to 97% in an observational study.…”
mentioning
confidence: 99%
“…Warm water was infused in lieu of air insufflation as the "principal modality" to decrease the discomfort of colonoscope insertion. Warm to touch tap water or water at body temperature (37 o C maintained by a water bath) was used because data in one publication support its effect in minimizing colonic spasms. The warm water was infused through the biopsy channel using a peristaltic pump via a tube fitted with a blunt needle adaptor.…”
mentioning
confidence: 99%
“…[10] In their very comprehensive study including more than 50,000 cases, Bannert et al [7] have shown that colonoscopy performed under sedation increased CIR in both men and women. Radaelli et al [11] reported that, CIR in colonoscopies with sedation and without sedation are in turn 84.2% and 76.1%. This rate is quite low when compared to ours.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of pediatric and variable stiffness instruments was evaluated in so-called "difficult colonoscopies" [3][4][5] as well as the use of sedation/analgesia and the level of sedation [6][7][8], the effectiveness of different methods of bowel preparation and the effect of colonoscopist experience [9]. Some studies attempted to investigate the possible influence of different instruments on cecal intubation rate and time [6].…”
Section: Introductionmentioning
confidence: 99%